Improving the Effectiveness of Help Desk Service Management in the Self-Service System at the UIN Sunan Ampel Surabaya Academic Library - Al Ghifary, Muhammad Fawaid; Amin, Faris Mushlihul; Ridwan, Mujib; Solakhudin, Muhammad Rafi (Jurusan Teknik Elektro, Universitas Bangka Belitung, 2025)
The increasing reliance on self-service systems in academic libraries necessitates robust service desk man-agement to ensure user satisfaction and operational efficiency. At the UIN Sunan Ampel Library, self-service systems provide convenient access to various services, but their performance remains underexplored. Evaluat-ing the library's service desk management using the ITIL V4 framework reveals critical insights into its effec-tiveness and areas for improvement. The framework’s Service Desk Practice Success Factors (PSF)—Acknowledge, Classify, Own, and Act—are used to assess how well self-service systems align with ITIL best practices. This research adopts a qualitative descriptive methodology, utilizing interviews and data analysis to evaluate service desk processes. The findings indicate significant benefits in accessibility and user empower-ment through self-service features. However, challenges persist, including manual acknowledgment workflows, insufficient SLA implementation, and limited real-time monitoring capabilities. These issues hinder optimal service delivery and responsiveness. To address these gaps, the study recommends integrating automation for acknowledgment tasks, developing measurable SLA policies, and implementing comprehensive training for library staff. Additionally, real-time tracking tools should be incorporated to enhance system efficiency and user experience. Despite these challenges, the study underscores the potential of ITIL V4 to improve library service desk management, ultimately fostering better user satisfaction and operational excellence.